2018
DOI: 10.1590/0100-29452018023
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock on production and quality of ‘Niagara Rosada’ grapevine

Abstract: Abtract In Brazil, the producers have changed used rootstocks to get more vigor to scion. Rootstocks change the distribution of bud fruitfulness over grapevine shoots and the expression of the bud fruitfulness into fruit yield. Hence, these modification could alter ideal pruning length. In this way, it was evaluated bud fruitfulness, fruit yield and quality of ‘Niagara Rosada’ grapevine grafted onto rootstocks: ‘IAC 766’, ‘IAC 572’, ‘IAC 313’, ‘IAC 571-6’, and ‘Riparia do Traviu’, which ‘IAC 766’ is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The rootstock IAC 572 had the largest mean stem diameter (35.01 mm), larger than that of Paulsen 1103, SO4, and 101-14 MgT. IAC 572 is characterized by high vigor, which induces the scion cultivars grafted onto it (Angelotti-Mendonça et al 2018, Embrapa 2023a, Pimentel Junior et al 2018, though this may be a characteristic restrictive to its use, since plants with very high vigor tend to decrease bud fertility and, consequently, fructification potential (Leão and Rodrigues 2015). However, under the conditions of this study, this trend was not observed, since the rootstock IAC 572 and IAC 766 led to an increase in the bud fertility index of 'BRS Melodia' grapevines in relation to Ramsey, and neither one differed from the other rootstocks studied.…”
Section: Resultsmentioning
confidence: 97%
“…The rootstock IAC 572 had the largest mean stem diameter (35.01 mm), larger than that of Paulsen 1103, SO4, and 101-14 MgT. IAC 572 is characterized by high vigor, which induces the scion cultivars grafted onto it (Angelotti-Mendonça et al 2018, Embrapa 2023a, Pimentel Junior et al 2018, though this may be a characteristic restrictive to its use, since plants with very high vigor tend to decrease bud fertility and, consequently, fructification potential (Leão and Rodrigues 2015). However, under the conditions of this study, this trend was not observed, since the rootstock IAC 572 and IAC 766 led to an increase in the bud fertility index of 'BRS Melodia' grapevines in relation to Ramsey, and neither one differed from the other rootstocks studied.…”
Section: Resultsmentioning
confidence: 97%
“…Although the stem is also an energy reserve organ for the plant, the reduction of the growth rate observed between the last two evaluated cycles can be considered normal, because with the age advancement and the consec-utive production cycles, the plants in general try to restore their reserves preferably in the roots. Most of the authors consider the vine vigor as being only the vegetative biomass removed during the pruning, not measuring other important characteristics such as the stems and branches secondary growth (ANGELOTTI-MENDONÇA et al, 2018;LEÃO et al, 2020b). It is important to highlight that the fresh mass obtained during the production pruning should not be the only measure to estimate the vine vigor, since the amount of material produced depends on other factors, such as the branch diameter, number of buds, energy reserves left after the previous productive cycle, rest period among crops and edaphoclimatic conditions (KELLER, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The immature berries bear white and green stripes running along the length of the fruit. Considering these extremely different traits, the mutant shoots were propagated by hardwood cuttings and have been kept in the grape collection as new varieties and have ever since been studied with different approaches (Sousa, 1959;Sousa, 1996;Tofanelli et al, 2011;Angelotti-Mendonça et al, 2018).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%